Analysis of the Effect of System Quality, Information Quality, and Service Quality on User Satisfaction of T24 Application (Temenos Transact Core Banking) with Perceived Usefulness as an Intervening Variable (Case Study: J Trust Bank Indonesia) - Budi Prasetya; Dimas Prayogo Mahardhika; Wendi Usino (Indonesian Interdisciplinary Journal of Sharia Economics)
This study aims to analyze the effect of system quality, information quality, and service quality on user satisfaction of the T24 application (Temenos Transact Core Banking) with perceived usefulness as an intervening variable, with a case study at J Trust Bank Indonesia. The research sample consisted of 113 respondents who were users of the T24 application. The analysis method used was Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that information quality did not have a significant effect on user satisfaction and perceived usefulness. Service quality had a significant effect on user satisfaction and perceived usefulness, with influence coefficients of 0.430 and 0.448, respectively. In addition, system quality had a significant effect on perceived usefulness (0.353), but did not have a direct effect on user satisfaction. Perceived usefulness was shown to have a significant effect on user satisfaction (0.268). The mediation relationship through perceived usefulness on user satisfaction shows that information quality, service quality and system quality do not have a significant effect with each P-Value of (0.428), (0.066) and (0.065). This study reveals the importance of service quality as a major factor in increasing user satisfaction with the support of system quality to strengthen the perception of the benefits of using the T24 application.